Aplikasi Aljabar Max-Plus dan Petri Net dalam Penentuan Waktu Optimal Produksi Tempe di Pabrik Tempe Asli Hb Samarinda - Khairina, Isna Nadia; A'yun, Qonita Qurrota; Sandariria, Hardina (Journal of Mathematics Education and Science, 2025)
Production time efficiency plays an important role in the food industry, including at the Tempe Asli HB Samarinda factory. The tempeh production process involves several lengthy stages, such as the preparation of raw materials, fermentation, and acidification. To optimize scheduling, Max-Plus algebra can be applied to enhance the effective and efficient use of production time. This study aims to construct a model of the tempeh production system using Petri Nets and to solve the tempeh production time problem by optimizing production time using Max-Plus Algebra. The research data was obtained through interviews with the branch manager of the Tempe Asli HB Samarinda factory. Petri nets were used to construct a coverability tree, which was subsequently transformed into a Max-Plus Algebra model. Subsequently, a model simulation was performed using production time data starting at t. The results of this research indicate that the optimal or minimum production time for tempeh is 3 days 6 hours and 57 minutes after production begins.